Discourse Production of #KaburAjaDulu on TikTok: A Critical Discourse Analysis of Awbimax Content - Sitti Amar Azizyah Puthe Taliu; Filosa Gita Sukmono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The #KaburAjaDulu hashtag on TikTok reflects a form of digital social criticism expressed by Indonesian youth toward socio-economic and political conditions in Indonesia. This discourse represents disappointment with economic inequality, public services, and declining trust in state institutions, while positioning migration as a rational response to uncertainty. This study aims to analyze how the #KaburAjaDulu discourse is constructed through Awbimax’s TikTok content using Fairclough’s CDA approach. This research employs a qualitative method by examining five purposively selected TikTok videos uploaded between October 2023 and February 2025. Data were collected through non-participant observation of video narration, captions, hashtags, visual elements, and audience comments. The analysis was conducted through three dimensions of CDA: textual analysis, discursive practice, and sociocultural practice. The findings show that the discourse is constructed through confrontational yet relatable language, casual visual representation, and repetitive narratives that normalize escapism as a rational individual choice. Socioculturally, the discourse reflects a shift from collective nationalism toward pragmatic individualism and reveals a growing crisis of trust between citizens and the state in the digital era.